2021
DOI: 10.3389/fpls.2021.657323
|View full text |Cite
|
Sign up to set email alerts
|

The Highs and Lows of P Supply in Medical Cannabis: Effects on Cannabinoids, the Ionome, and Morpho-Physiology

Abstract: Environmental conditions, including the availability of mineral nutrients, affect secondary metabolism in plants. Therefore, growing conditions have significant pharmaceutical and economic importance for Cannabis sativa. Phosphorous is an essential macronutrient that affects central biosynthesis pathways. In this study, we evaluated the hypothesis that P uptake, distribution and availability in the plant affect the biosynthesis of cannabinoids. Two genotypes of medical “drug-type” cannabis plants were grown un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
75
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(99 citation statements)
references
References 105 publications
(164 reference statements)
10
75
1
Order By: Relevance
“…In the study from Yang et al [ 17 ], similar trends for a plateau of total CBD concentrations in the studied range of harvest times were reported for five CBD-rich cannabis genotypes grown in open-field. All five genotypes presented an increasing trend of total CBD concentration until a peak by six to seven weeks of flowering.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…In the study from Yang et al [ 17 ], similar trends for a plateau of total CBD concentrations in the studied range of harvest times were reported for five CBD-rich cannabis genotypes grown in open-field. All five genotypes presented an increasing trend of total CBD concentration until a peak by six to seven weeks of flowering.…”
Section: Resultssupporting
confidence: 76%
“…The importance of optimizing indoor systems has increased due to the demand for yield maximization and improved efficiency of growing systems [ 13 ]. Final yield quantity and quality of inflorescences are highly variable and depends on numerous factors such as genotype [ 14 , 15 , 16 ]; the agronomic practices, such as irrigation and fertilizer regimes [ 17 , 18 , 19 , 20 ], light spectra [ 14 , 21 ], intensity [ 22 , 23 ] and photoperiod [ 24 ]; plant density [ 25 ]; environmental conditions (humidity and temperature) [ 12 ] and the influence of biotic and abiotic stresses [ 26 , 27 ]—including pruning and defoliation techniques [ 28 , 29 ]—and finally, the duration of the vegetative and generative period. Thus, so many differences can be found for reported yield of medicinal cannabis currently in literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the potential for production of a specific secondary metabolite profile in cannabis is determined by the genetic background of the plant [4], the actual levels of the produced metabolites are affected to a large extent by environmental conditions during cultivation, such as mineral nutrition [4][5][6][7], light intensity and light spectrum [8,9], and elicitation of stress conditions [10]. Variability in the chemical profile between inflorescences was observed also along the plant [4,6,7,11]. Furthermore, as plant organs sense their environments locally, differences between micro-climates within the shoot further induce changes in physiology [12] and secondary metabolism [13].…”
Section: Introductionmentioning
confidence: 99%
“…Using gene silencing tools, designer strains with high levels of CBD producing zero THC are possible, as are strains with elevated levels of CBG, which contains anti-cancer properties ( Borrelli et al, 2014 ), through the knockdown of the downstream enzymatic processes of THCAS, CBDAS , and CBCAS . The use of environmental pressures applied through varying nutrient concentrations ( Saloner and Bernstein, 2021 ; Shiponi and Bernstein, 2021 ) or light spectrum and lighting source ( Magagnini et al, 2018 ; Namdar et al, 2019 ) has previously demonstrated significant modulation of secondary metabolites, up to 300% in some instances ( Shiponi and Bernstein, 2021 ). While this ability to variably control cannabinoid content in cannabis using environmental conditions is significant, the synergistic effects of all cannabinoids either increasing or decreasing make this approach incapable of producing a complete knockdown/significant downregulation of specific cannabinoids to create novel chemotypes.…”
Section: Introductionmentioning
confidence: 99%